Review of dairy marketing and processing in a semi-arid pastoral system in Ethiopia - Coppock, D. Layne; Holden, S.J.; Assefa, M. (International Livestock Centre for Africa, 1992)
Studies were conducted among pastoralists on the Borana Plateau in 1986-89. Household surveys described seasonal milk production and allocation, marketed supply of dairy products, incidence of calf morbidity and mortality and human consumption of dairy products and grain. The efficiency of butter-making was measured. Dairying among the Borana is controlled by the women. Overall, 69 percent of milk produced was used as fresh milk and the remainder was soured for direct consumption or butter processing. Butter-making is efficient, as 85 percent of the fat in whole milk was recovered as butter. The amount of milk sold was greatest in the wet seasons and wealthy families close to markets sold the largest quantities, consisting of fresh milk and butter. Poor families sold much less, mostly fresh milk. Dairy income was relatively more important for the poor, who used the money to purchase grain at the expense of calf welfare and balanced human nutrition. Dairy marketing is a dynamic process that varies with climate and population pressure. Policies that facilitate market access and increase the trading value of dairy products would improve food security. Technical interventions to improve milk processing and largely irrelevant at the current population density because milk surplus are becoming smaller as a result of growth in the human population exceeding that of the cattle population